Enhancement of Power Management in Microgrid Systems - Chatterjee, Sayan; Baheti, Gaurang; Hota, Ansuman (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
A microgrid may be a localized cluster of sources and power bank of energy that sometimes runs coupled with the standard synchronous wide-area grid. It also has the ability to disengage from "island mode" and work independently when physical or economic conditions require it. Micro grids have the ability to eliminate the stress from the primary transmission networks, minimize feeder losses, improve system power quality (PQ), and improve power management. Micro grid power management is difficult due to the use of energy storage and generic components such as PV, diesel generators, micro-hydro generators, and a directly inverter with an energy battery bank. In this research, the suggested droop controller is used to assess the power distribution of the Micro grid. The droop controller is designed to ensure that the Micro grid’s energy management is as efficient as possible. The management of power is done via droop on the generation side. The load demand of the grid side is controlled by the control action of actual and reactive power. The project’s goal is to use the DIgSILENT Power Factory to boost the Micro grid’s actual and reactive power. The simulation for the 6 bus Micro grid test system with actual and reactive power sharing during islanding and grid linked mode was successfully completed.